1998
DOI: 10.1021/jm9704661
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in Vitro Efficacy of Transferrin Conjugates of the Anticancer Drug Chlorambucil

Abstract: One strategy for improving the selectivity and toxicity profile of antitumor agents is to design drug carrier systems employing soluble macromolecules or carrier proteins. Thus, five maleimide derivatives of chlorambucil were bound to thiolated human serum transferrin which differ in the stability of the chemical link between drug and spacer. The maleimide ester derivatives 1 and 2 were prepared by reacting 2-hydroxyethylmaleimide or 3-maleimidophenol with the carboxyl group of chlorambucil, and the carboxylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 17 publications
1
51
0
1
Order By: Relevance
“…Our time-dependent stability studies with the active acid-sensitive conjugates Tf-Hyd 1 and Tf-Hyd 2 in 10% FCS and "cell-conditioned" cell culture medium rule out the possibility that their antiproliferative activity is due to a rapid hydrolysis of the hydrazone bond realized in the conjugates as only very small amounts of doxorubicin are released under these conditions during 24 h. The importance of the acidsensitivity of the linker between doxorubicin and the carrier protein for anticancer activity has been noted by Greenfield et al 32 and by our group for acid-sensitive daunorubicin and chlorambucil conjugates. 33, 34 Faulk has prepared transferrin conjugates in which doxorubicin is bound to transferrin through glutaraldehyde coupling, 15 the chemical link between transferrin and the amino sugar position of doxorubicin presumably being realized by an imine bond. From a chemical point of view this bond exhibits acid-sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Our time-dependent stability studies with the active acid-sensitive conjugates Tf-Hyd 1 and Tf-Hyd 2 in 10% FCS and "cell-conditioned" cell culture medium rule out the possibility that their antiproliferative activity is due to a rapid hydrolysis of the hydrazone bond realized in the conjugates as only very small amounts of doxorubicin are released under these conditions during 24 h. The importance of the acidsensitivity of the linker between doxorubicin and the carrier protein for anticancer activity has been noted by Greenfield et al 32 and by our group for acid-sensitive daunorubicin and chlorambucil conjugates. 33, 34 Faulk has prepared transferrin conjugates in which doxorubicin is bound to transferrin through glutaraldehyde coupling, 15 the chemical link between transferrin and the amino sugar position of doxorubicin presumably being realized by an imine bond. From a chemical point of view this bond exhibits acid-sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…And preliminary toxicity studies in mice showed that this conjugate can be administrated at higher doses compared with unbound chlorambucil. 186 Transferrin-mitomycin C (MMC), the chemotherapeutic DNA crosslinking agent, has been demonstrated to be a useful hybrid as a receptor-mediated targeting system. [187][188][189] The Tf-MMC conjugate bound and was internalized into the human hepatoma cell line HepG2 cell, normal cultures rat hepatocyte, human leukemia cell line HL60 cells and Sarcoma 180 cells.…”
Section: A Transferrin Conjugates In Drug Deliverymentioning
confidence: 99%
“…The Kratz group has also used transferrin [124] and albumin [125] as carriers for the targeting of the anticancer drug chlorambucil (Fig. 45).…”
Section: -Hydrazone Linkagesmentioning
confidence: 99%